FAKTOR -FAKTOR YANG MEMPENGARUHI INTENTION TO VISIT KOTA BATAM - Purwianti, Lily (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
The tourism sector is an important sector for a country, because it can benefit many people such as the economic sector that can attract tourists and investors to continue to work with the country. The object of research in this study is the foreign tourists who visit Batam as their destination destination by using the method of Purposive Sampling, the sample must meet the characteristics of the main objectives in the study. This research uses Statistical Package for Social Sciences or (SPSS) application to analyze the influence of independent variable to dependent variable. The result of this research indicate that attitude, subjective norm, perceived behavioral control variables significantly influence intention to visit and ideal social and destination familiarization variable there is no significant influence to dependent variable that is intention to visit